Science and technology roadmap for graphene, related two-dimensional crystals, and hybrid systems. Issue 11 (21st March 2015) - Ferrari, Andrea C.; Bonaccorso, Francesco; Fal'ko, Vladimir; Novoselov, Konstantin S.; Roche, Stephan; Bøggild, Peter; Borini, Stefano; Koppens, Frank H. L.; Palermo, Vincenzo; Pugno, Nicola; Garrido, José A.; Sordan, Roman; et al.
<x xml:space="preserve">Abstract</x> We present the science and technology roadmap for graphene, related two-dimensional crystals, and hybrid systems, targeting an evolution in technology, that might lead to impacts and benefits reaching into most areas of society.